2018
DOI: 10.1111/pce.13158
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting acclimation abilities of two dominant boreal conifers to elevated CO2 and temperature

Abstract: High latitude forests will experience large changes in temperature and CO concentrations this century. We evaluated the effects of future climate conditions on 2 dominant boreal tree species, Pinus sylvestris L. and Picea abies (L.) H. Karst, exposing seedlings to 3 seasons of ambient (430 ppm) or elevated CO (750 ppm) and ambient temperatures, a + 4 °C warming or a + 8 °C warming. Pinus sylvestris responded positively to warming: seedlings developed a larger canopy, maintained high net CO assimilation rates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 57 publications
(110 reference statements)
4
32
1
Order By: Relevance
“…Lower protein concentrations may also explain why warm‐grown trees showed reduced photosynthetic rates and lower chlorophyll fluorescence ( F v ʹ/ F m ʹ, Φ PSII ) at a common measurement temperature, compared to cool‐grown trees. Previous studies have found evidence of positive, neutral, and negative responses of photosynthetic capacity with increasing temperatures (Aspinwall et al, ; Kurepin et al, ; Way & Yamori, ), which may be associated with changes in leaf enzyme concentrations. Most importantly, lower concentrations of metabolic (i.e., respiratory) and stress avoidance (i.e., redox, superoxide dismutase) proteins may have hindered warm‐grown trees ability to cope with heatwave conditions (Alscher, Erturk, & Heath, ; Wang, Heckathorn, Mainali, & Hamilton, ; Wang, Zhang, Goatley & Ervin, ).…”
Section: Discussionmentioning
confidence: 92%
“…Lower protein concentrations may also explain why warm‐grown trees showed reduced photosynthetic rates and lower chlorophyll fluorescence ( F v ʹ/ F m ʹ, Φ PSII ) at a common measurement temperature, compared to cool‐grown trees. Previous studies have found evidence of positive, neutral, and negative responses of photosynthetic capacity with increasing temperatures (Aspinwall et al, ; Kurepin et al, ; Way & Yamori, ), which may be associated with changes in leaf enzyme concentrations. Most importantly, lower concentrations of metabolic (i.e., respiratory) and stress avoidance (i.e., redox, superoxide dismutase) proteins may have hindered warm‐grown trees ability to cope with heatwave conditions (Alscher, Erturk, & Heath, ; Wang, Heckathorn, Mainali, & Hamilton, ; Wang, Zhang, Goatley & Ervin, ).…”
Section: Discussionmentioning
confidence: 92%
“…With climatedriven earlier bud flush and an increase in frequency of spring backlash events 45 , Norway spruce is likely to be more vulnerable to spring frost damage to their canopy in the coming years. It has also recently been shown that Scots pine is more able than Norway spruce to acclimate photosynthesis and respiration to both increased seasonal temperatures and elevated CO 2 46 . Scots pine increased growth in response to temperature increases as high as +8°C, whereas Norway spruce showed minimal capacity to acclimate energy metabolism and suffered growth losses at elevated seasonal temperatures 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been shown that Scots pine is more able than Norway spruce to acclimate photosynthesis and respiration to both increased seasonal temperatures and elevated CO 2 46 . Scots pine increased growth in response to temperature increases as high as +8°C, whereas Norway spruce showed minimal capacity to acclimate energy metabolism and suffered growth losses at elevated seasonal temperatures 46 . These findings, together with those we report here, indicate that the pioneer species Scots pine may generally have a greater capacity to cope with environmental fluctuations and challenges than the more ecologically conservative late successional species Norway spruce.…”
Section: Discussionmentioning
confidence: 99%
“…However, while some studies find similar responses of carbon dynamics across species to warming and CO 2 (Xu et al, 2014), the variation in how species respond to climate treatments can be substantial, even within a single PFT (Reich et al, 1998). When both Scots pine and Norway spruce were grown at a range of elevated temperatures and CO 2 concentrations, pine showed thermal acclimation of A net and respiration, and thus maintained high net carbon uptake rates at higher temperatures, while A net and respiration showed little acclimation to either CO 2 or warming in spruce, leading to a suppression of net carbon gain in warm-grown spruce trees (Kurepin et al, 2018). As we move forward, it is therefore important to consider not only the mean responses on plant carbon fluxes to climate change, but also the extreme responses, especially when they occur in species with outsized ecological or agricultural impact.…”
Section: Reviewmentioning
confidence: 99%